2009
DOI: 10.3899/jrheum.080699
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Low Bone Mineral Density and Varus Deformity in Postmenopausal Women with Knee Osteoarthritis

Abstract: Varus inclination of the tibial plateau was significantly more severe in the femorotibial angle tertile 3 group, and in patients with lower BMD in the ipsilateral lower limb. Varus knee OA may result not only from cartilage loss but also from structural changes of the bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
(21 reference statements)
2
17
0
2
Order By: Relevance
“…In addition, similar to the case of the femoral neck, the SONK group had significantly lower BMDs at the lateral femoral and lateral tibial condyles than the OA group. The lateral condyle BMDs represent the BMD of the ipsilateral lower extremity in all of the knee condyles, as we found in a previous study (Akamatsu et al 2009). These findings therefore suggest that recent onset of SONK has an association with low BMD in women over 60 years.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, similar to the case of the femoral neck, the SONK group had significantly lower BMDs at the lateral femoral and lateral tibial condyles than the OA group. The lateral condyle BMDs represent the BMD of the ipsilateral lower extremity in all of the knee condyles, as we found in a previous study (Akamatsu et al 2009). These findings therefore suggest that recent onset of SONK has an association with low BMD in women over 60 years.…”
Section: Discussionsupporting
confidence: 56%
“…The decreases in lateral femoral and tibial condyle BMDs with advancing age could be attributed to general osteoporosis. We stated in a previous study that lateral tibial condyle BMD is probably a better reflection of BMD at the knee than medial tibial condyle BMD (38); furthermore, the decreased lateral condyle BMDs with age may represent a postmenopausal decrease in the general BMD. Alternatively, the finding that the medial condyle BMDs did not decrease with age might result in subchondral bone sclerosis, followed by the progression of medial knee OA with age.…”
Section: Discussionmentioning
confidence: 87%
“…At later stages, after the subchondral bone has been exposed, deformation occurs as a result of subchondral bone plate microfractures, suggesting that changes in the subchondral bone may play a larger role than that played by changes in the underlying trabeculae (3). Moreover, the association between varus inclination of the tibial plateau and low BMD suggests that microfractures may occur before the eburnation of the subchondral bone (38, 44). In addition, previous experimental data have revealed that edema of the medial bone marrow, which was identified on MRI, is associated with varus deformities in patients with medial knee OA (45), but it is unknown whether edema of the bone marrow affects structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most common joint disease and is characterized by a progressive loss of cartilage, changes in the subchondral bone, inactivity-related stiffness, and chronic pain [1,2,3,4]. Although pain is the predominant clinical feature of OA, the specific source and molecular events responsible for originating the pain from the OA joint are not yet completely understood [5].…”
Section: Introductionmentioning
confidence: 99%